Communicating Marketing and Advocacy Research to Practice - Haddow, Gaby (IFLA, 2010)
This paper reports on a study that explored the role of library associations in the communication of marketing and advocacy research to practice. Support for making research information accessible to practitioners through library associations’ publications can be found in previous studies which examined the relationship between LIS practitioners and research. Using content analysis and literature searches, the current study expands on these findings to determine the extent and nature of marketing and advocacy research available to practitioners. The results indicate that marketing and advocacy research is rarely communicated to practitioners through two associations’ publications. However, marketing research information for nonprofit service organisations, generally, is not widely available. Drawing on the study’s findings and research communication strategies used in other contexts, the paper concludes by making recommendations for future initiatives to improve practitioner access to advocacy and marketing research information.